Télématique et assurance - Dumont, Monique (Assurances)

(untitled) (HEC Montréal, 1982)
Miss Monique Dumont describes the latest progress in the field of telecommunications and in particular the results obtained from the use of "videotex" in those countries which are the most advanced in this field. She analyses the caracteristics and the advantages of, in particular, Telidon (Canada) and Prestel (United Kingdom). The author describes the services provided by and limitations of these systems, and the extraordinary success of Preslel in the United Kingdom, particularly with commercial firms. She describes the possible implications for the insurance world and ends with a reference to several interesting articles.